The Actual Mobility Paradigm, the new cars and the purchase challenge - Gouveia, Eduardo; Santos, Vasco (Millenium - Journal of Education, Technologies, and Health, 2022)
Nowadays, there is a paradigm about energy solutions concerning their cost and environmental impact, both aspects related to their efficiency. If for the UN and the EU, the main challenges are the promotion of sustainability and the decarbonisation of society, for the typical user, facing an energy crisis and other “phenomena” derived from the international situation, the value paid for energy is an fundamental aspect. If, on the one hand, there is a need to define good practices and behavioural change, on the other hand, the costs of energy vectors can compromise this objective. An example of this situation can be the “wave” of inflation that abounds across Europe, leveraged by the fuel crisis resulting from the war in Ukraine and market speculation. Thus Institutions assume a fundamental role and must be the mechanism for a profound reflection on the challenges society faces today and the consequences for future generations regarding complex processes related to globalization, climate change, energy dependencies, geostrategic conflicts, migrations, and digitalization, in sectors as diverse as food, health, housing, and transport. For this reason, institutions must create political, economic, technical, and other mechanisms that allow the common user to adopt good practices and make informed decisions.